SQST-1/p62-regulated SKN-1/Nrf mediates a phagocytic stress response via transcriptional activation of lyst-1/LYST - Elkhalil, Aladin; Whited, Alec; Ghose, Piya (PLoS genetics, 2025)
Cells may be intrinsically fated to die to sculpt tissues during development or to maintain homeostasis. Cells can also die in response to various stressors, injury or pathological conditions. Additionally, cells of the metazoan body are often highly specialized with distinct domains that differ both structurally and with respect to their neighbors. Specialized cells can also die, as in normal brain development or pathological states and their different regions may be eliminated via different programs. Clearance of different types of cell debris must be performed quickly and efficiently to prevent autoimmunity and secondary necrosis of neighboring cells. Moreover, all cells, including those programmed to die, may be subject to various stressors. Some largely unexplored questions include whether predestined cell elimination during development could be altered by stress, if adaptive stress responses exist and if polarized cells may need compartment-specific stress-adaptive programs. We leveraged Compartmentalized Cell Elimination (CCE) in the nematode C. elegans to explore these questions. CCE is a developmental cell death program whereby three segments of two embryonic polarized cell types are eliminated differently. We have previously employed this in vivo genetic system to uncover a cell compartment-specific, cell non-autonomous clearance function of the fusogen EFF-1 in phagosome closure during corpse internalization. Here, we introduce an adaptive response that serves to aid developmental phagocytosis as a part of CCE during stress. We employ a combination of forward and reverse genetics, CRISPR/Cas9 gene editing, stress response assays and advanced fluorescence microscopy. Specifically, we report that, under heat stress, the selective autophagy receptor SQST-1/p62 promotes the nuclear translocation of the oxidative stress-related transcription factor SKN-1/Nrf via negative regulation of WDR-23. This in turn allows SKN-1/Nrf to transcribe lyst-1 /LYST (lysosomal trafficking associated gene) which subsequently promotes the phagocytic resolution of the developmentally-killed internalized cell even under stress conditions.